Women, Research and Methods. A Short Reflection on The Chicago Social Reformers - Cersosimo, Giuseppina (Italian Sociological Review, 2021)
This paper is a brief reflection on the presence of women such as Jane Addams, Florence Kelley, Alice Hamilton, and other female reformers of Hull-House, an emblem of the growing female presence in social analysis from the year 1889 ahead. It is not our goal to extol the feminist pragmatism of women active in Chicago – outside the University – but rather to consider the activity of those women in terms of the real characteristics of their position in the field of American Sociology; expecially in relation to investigations linked to the rights of individuals, women and children, and for their special contribution to the methods of their research.